Basic periodontitis manual: what it is, symptoms and treatments. - Coelho Paraguassu, Eber (Brazilian Journal of Implantology and Health Sciences, 2023)
Periodontitis is an inflammation and chronic infection in the gum, caused by the accumulation of plaque or tartar between the teeth and the gum, and excessive proliferation of bacteria, which over time, results in the destruction of the tissue that supports the tooth, which may affect a or more teeth. Periodontitis can be noticed by swelling in the gum, which can also be red and bleed during brushing and eating. Also, when you observe that your teeth are becoming crooked or gradually separated, it may be a sign that the supporting tissues of your teeth are weakened. It is important to consult the dentist whenever symptoms of periodontitis appear so that the diagnosis is made and the most appropriate treatment is indicated, which can be done with removal of bacterial plaque and tartar, use of antibiotics or surgery. Image 1: Teeth with generalized periodontitis. Symptoms of periodontitis The main symptoms of periodontitis are: - Bad breath; - Very red gums; - Swollen gums; - Gum bleeding after brushing your teeth or eating; - Red and swollen gums; - Crooked teeth; - Teeth softening; - Increased tooth sensitivity; - Loss of teeth; - Increased space between teeth; - Waking up with blood on the pillow. Periodontitis can be localized, affecting only one or the other tooth, or generalized, when it affects all teeth at the same time. The change in the appearance of the teeth is what most attracts the attention of the person, or people close to them. Most people suffer from an episode of gum inflammation at least once in their lives, being particularly common in women during pregnancy, due to hormonal changes, but not everyone will have periodontitis, which despite having gingivitis as a symptom, is a more serious condition, which may even require deep scaling of the gums and dental surgery. How to confirm the diagnosis The diagnosis of periodontitis can be made by the dentist by observing the person's teeth and gums, and assessing the health history, to identify lifestyle habits or use of medicines that may be leading to the emergence of symptoms. In addition, to confirm periodontitis, the dentist should request an image exam, such as a panoramic X-ray, in order to assess the bone loss in the affected region. Learn how the panoramic X-ray is done. Possible causes The main cause of periodontitis is the formation of bacterial plaque and tartar on the teeth and between the teeth and the gums, causing chronic inflammation in the gums, and the development of pockets containing bacteria, plaques and tartar, between the gums and the teeth, which can lead to deep infections and loss of bone tissue. Some factors can increase the risk of developing periodontitis, such as: - Poor oral hygiene; - Habit of smoking or chewing tobacco; - Hormonal changes in pregnancy or menopause; - Electronic cigarette or VAPE use; - Vitamin C deficiency; - Type 2 diabetes; - Obesity; - Rheumatoid arthritis; - Crohn's disease; - Use of oral contraceptives; - Use of drugs that reduce saliva production, such as antihistamines, antidepressants or antihypertensives. In addition, genetic factors or diseases that affect the immune system, such as HIV infection or leukemia, can also increase the risk of developing periodontitis. Treatment of periodontitis Treatment to end periodontitis involves scraping the root of the tooth, in the office and under anesthesia, to remove tartar plaque and bacteria that are destroying the bone structure that supports the tooth. The use of antibiotics may be part of the treatment in some cases. Maintenance at the dentist periodically decreases the evolution of this inflammation and helps to control the disease, reducing bone loss and preventing tooth loss. In addition, not smoking, brushing your teeth daily and flossing are ways to control and cure periodontitis.